Optical glass
By optimizing the component design of optical glass, combined with SiO2, Al2O3, ZrO2, BaO and other components, the problem of difficult to take into account the anti-crystalline performance and high-temperature viscosity in large-diameter vehicle-mounted security lenses, and the light transmittance and overall glass are improved performance.
Patent Information
- Application Number
- CN202310696547.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-13
AI Technical Summary
In the existing optical glass with large diameter and high definition automotive security lenses, it is difficult to take into account both the crystallization resistance and high temperature viscosity, and the transmittance is insufficient.
By optimizing the component design, it contains SiO2, Al2O3, ZrO2, BaO, TiO2, ZnO and other ingredients, control the proportion of each component, reasonably combine B2O3, CaO, SrO, Na2O, MgO, Li2O, K2O, WO3, Nb2O5 and clarifiers, and optimizes the Chemical stability and optical properties of glass.
It achieves a low high-temperature viscosity and excellent crystallization resistance, which improves the light transmittance and overall performance of the glass.
Smart Images

Figure BDA0004281954470000131 
Figure BDA0004281954470000161 
Figure BDA0004281954470000171
Abstract
Description
Technical Field
[0001] The invention relates to an optical glass, in particular to an optical glass with excellent anti-crystallization performance and low high-temperature viscosity. Background Art
[0002] Optical glass with a refractive index of 1.67-1.73 and an Abbe number of 38-45 belongs to heavy barium flint glass, which is widely used in the design of optical lenses for security and automotive applications to improve the imaging quality of optical systems. In recent years, automotive security lenses have developed in the direction of large aperture and high definition, which requires larger aperture and higher transmittance of optical lenses. The substantial increase in lens aperture requires glass materials to have excellent anti-crystallization performance and light transmittance. Chinese patent CN107555785A discloses an optical glass with a refractive index of 1.61-1.70 and an Abbe number of 36-47, which contains a large amount of components such as B2O3 and Nb2O5, and its properties such as high temperature viscosity need to be further optimized. Summary of the invention
[0003] The technical problem to be solved by the present invention is to provide an optical glass with excellent anti-crystallization performance and low high-temperature viscosity.
[0004] The technical solution adopted by the present invention to solve the technical problem is:
[0005] Optical glass, whose components are expressed in weight percentage, contains: SiO2: 25-35%; Al2O3: 0-8%; ZrO2: 2-10%; BaO: 35-45%; TiO2: 3-12%; ZnO: 6-15%.
[0006] Furthermore, the optical glass, whose components are expressed in weight percentage, also contains: B2O3: 0-8%; and / or CaO: 0-5%; and / or SrO: 0-5%; and / or Na2O: 0-5%; and / or MgO: 0-5%; and / or Li2O: 0-5%; and / or K2O: 0-5%; and / or WO3: 0-5%; and / or Nb2O5: 0-5%; and / or Ln2O3: 0-8%; and / or clarifier: 0-1%, wherein the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3, and the clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2.
[0007] The optical glass comprises, by weight percentage, 25-35% SiO2, 0-8% Al2O3, 2-10% ZrO2, 35-45% BaO, 3-12% TiO2, 6-15% ZnO, 0-8% B2O3, 0-5% CaO, 0-5% SrO, 0-5% Na2O, 0-5% MgO, 0-5% Li2O, 0-5% K2O, 0-5% WO3, 0-5% Nb2O5, 0-5% Ln2O3, and 0-1% clarifier, wherein the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3, and the clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2.
[0008] Furthermore, the components of the optical glass are expressed in weight percentage, wherein: (SiO2+BaO) / (ZrO2+Al2O3) is 3.5~15.0, preferably (SiO2+BaO) / (ZrO2+Al2O3) is 4.0~10.5, more preferably (SiO2+BaO) / (ZrO2+Al2O3) is 5.0~10.0, and further preferably (SiO2+BaO) / (ZrO2+Al2O3) is 6.0~9.5.
[0009] Furthermore, the components of the optical glass are expressed in weight percentage, wherein: TiO2 / (CaO+Al2O3) is 0.5~6.0, preferably TiO2 / (CaO+Al2O3) is 0.7~5.0, more preferably TiO2 / (CaO+Al2O3) is 0.8~4.0, and further preferably TiO2 / (CaO+Al2O3) is 1.0~3.0.
[0010] Furthermore, the components of the optical glass are expressed in weight percentage, wherein: ZrO2 / (CaO+TiO2+Al2O3) is 0.2~1.5, preferably ZrO2 / (CaO+TiO2+Al2O3) is 0.4~1.0, more preferably ZrO2 / (CaO+TiO2+Al2O3) is 0.45~0.9, and further preferably ZrO2 / (CaO+TiO2+Al2O3) is 0.5~0.8.
[0011] Furthermore, the components of the optical glass are expressed in weight percentage, wherein: (SiO2+CaO+SrO) / BaO is 0.56~1.05, preferably (SiO2+CaO+SrO) / BaO is 0.6~1.0, more preferably (SiO2+CaO+SrO) / BaO is 0.65~0.95, and further preferably (SiO2+CaO+SrO) / BaO is 0.7~0.95.
[0012] Furthermore, the components of the optical glass are expressed in weight percentage, wherein: (MgO+CaO+SrO) / ZrO2 is less than 1.5, preferably (MgO+CaO+SrO) / ZrO2 is less than 1.0, more preferably (MgO+CaO+SrO) / ZrO2 is 0.02~0.8, and further preferably (MgO+CaO+SrO) / ZrO2 is 0.05~0.5.
[0013] Furthermore, the components of the optical glass are expressed in weight percentage, wherein: (CaO+SrO) / ZnO is less than 1.0, preferably (CaO+SrO) / ZnO is less than 0.8, more preferably (CaO+SrO) / ZnO is less than 0.5, and further preferably (CaO+SrO) / ZnO is 0.01-0.3.
[0014] Furthermore, the components of the optical glass are expressed in weight percentage, wherein: BaO / (SiO2+B2O3+Li2O+CaO+SrO) is 0.65~1.5, preferably BaO / (SiO2+B2O3+Li2O+CaO+SrO) is 0.7~1.4, more preferably BaO / (SiO2+B2O3+Li2O+CaO+SrO) is 0.8~1.3, and further preferably BaO / (SiO2+B2O3+Li2O+CaO+SrO) is 0.9~1.2.
[0015] Furthermore, the components of the optical glass are expressed in weight percentage, wherein: (Li2O+Na2O+K2O) / ZrO2 is less than 1.0, preferably (Li2O+Na2O+K2O) / ZrO2 is less than 0.7, more preferably (Li2O+Na2O+K2O) / ZrO2 is 0.02~0.5, and further preferably (Li2O+Na2O+K2O) / ZrO2 is 0.1~0.4.
[0016] Furthermore, the components of the optical glass are expressed in weight percentage, wherein: Ln2O3 / TiO2 is less than 0.4, preferably Ln2O3 / TiO2 is less than 0.3, more preferably Ln2O3 / TiO2 is less than 0.2, and further preferably Ln2O3 / TiO2 is less than 0.1, and the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3.
[0017] Furthermore, the components of the optical glass are expressed in weight percentage, wherein: (B2O3+Ln2O3) / ZrO2 is less than 3.5, preferably (B2O3+Ln2O3) / ZrO2 is 0.1-3.0, more preferably (B2O3+Ln2O3) / ZrO2 is 0.2-2.5, and further preferably (B2O3+Ln2O3) / ZrO2 is 0.3-1.5, and the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3.
[0018] Furthermore, the components of the optical glass are expressed in weight percentage, wherein: (CaO+SrO+K2O+Ln2O3) / Al2O3 is less than 2.0, preferably (CaO+SrO+K2O+Ln2O3) / Al2O3 is less than 1.5, more preferably (CaO+SrO+K2O+Ln2O3) / Al2O3 is less than 1.1, and further preferably (CaO+SrO+K2O+Ln2O3) / Al2O3 is 0.02-0.8, and the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3.
[0019] Furthermore, the components of the optical glass are expressed in weight percentage, wherein: (CaO+TiO2) / Na2O is 2.0-20.0, preferably (CaO+TiO2) / Na2O is 4.5-16.0, more preferably (CaO+TiO2) / Na2O is 5.0-15.0, and further preferably (CaO+TiO2) / Na2O is 5.0-10.0.
[0020] Furthermore, the optical glass, its components are expressed in weight percentage, wherein: SiO2: 28-33%, preferably SiO2: 29-32%; and / or Al2O3: 1-6%, preferably Al2O3: 2-5%; and / or ZrO2: 3-8%, preferably ZrO2: 4-6%; and / or BaO: 36-43%, preferably BaO: 37-41%; and / or CaO: 0-3%, preferably CaO: 0.1-2%; and / or SrO: 0-2%, preferably SrO: 0-1%; and / or TiO2: 5-10%, preferably TiO2: 6-9%; and / or ZnO: 8-12%, preferably ZnO: 9-11%; and / or Na2O: 0-3%, preferably Na2O: 0.1-2%; and / or B2O3: 1-6%, preferably B2O3: 2-5%; and / or MgO: 0-2%, preferably MgO: 0-1%; and / or Li2O: 0-2%, preferably Li2O: 0-1%; and / or K2O: 0-2%, preferably K2O: 0-1%; and / or WO3: 0-2%, preferably WO3: 0-1%; and / or Nb2O5: 0-2%, preferably Nb2O5: 0-1%; and / or Ln2O3: 0-5%, preferably Ln2O3: 0-2%; and / or clarifier: 0-0.5%, preferably clarifier: 0-0.2%, wherein Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3, and the clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2.
[0021] Furthermore, the optical glass does not contain MgO in its components; and / or does not contain SrO; and / or does not contain Li2O; and / or does not contain K2O; and / or does not contain WO3; and / or does not contain Nb2O5; and / or does not contain SnO2; and / or does not contain SnO; and / or does not contain CeO2; and / or does not contain As2O3; and / or does not contain PbO; and / or does not contain Ln2O3, and the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3.
[0022] Furthermore, the refractive index n of the optical glass is d is 1.67 to 1.73, preferably 1.68 to 1.72, more preferably 1.69 to 1.71, and the Abbe number v d It is 38 to 45, preferably 39 to 44, and more preferably 40.5 to 42.5.
[0023] Furthermore, the density of the optical glass is 4.10 g / cm 3 Below, preferably 4.00 g / cm 3 Below, more preferably 3.90g / cm3 Below; and / or thermal expansion coefficient α 100 / 300℃ 95×10 -7 / K or less, preferably 90×10 -7 / K or less, more preferably 85×10 -7 / K or less; and / or water resistance stability D W 2 or more, preferably 1; and / or acid resistance stability D A The weather resistance CR is 2 or more, preferably 1; and / or the air bubble degree is A or more, preferably A0 or more, more preferably A 00 level; and / or transition temperature T g is 680°C or less, preferably 670°C or less, more preferably 665°C or less; and / or the crystallization upper limit temperature is 1100°C or less, preferably 1080°C or less, more preferably 1070°C or less; and / or the striae is C or above, preferably B or above; and / or the viscosity at 1400°C is 50 poise or less, preferably 1 to 40 poise, more preferably 2 to 20 poise; and / or the light transmittance τ 400nm It is 92.0% or more, preferably 93.0% or more, more preferably 94.0% or more, and further preferably 95.0% or more.
[0024] The glass preform is made of the above optical glass.
[0025] The optical element is made of the above optical glass, or made of the above glass preform.
[0026] An optical instrument contains the above optical glass and / or contains the above optical element.
[0027] The beneficial effects of the present invention are: through reasonable component design, the optical glass of the present invention has lower high-temperature viscosity and excellent anti-crystallization performance. DETAILED DESCRIPTION
[0028] The following will describe the embodiments of the optical glass of the present invention in detail, but the present invention is not limited to the following embodiments, and can be implemented by appropriate changes within the scope of the purpose of the present invention. In addition, although there are appropriate omissions of descriptions of the repeated descriptions, the gist of the invention will not be limited thereby, and in the following content, the optical glass of the present invention is sometimes referred to as glass.
[0029] [Optical glass]
[0030] The following is an explanation of the range of each component (ingredient) of the optical glass of the present invention. In the present invention, unless otherwise specified, the content and total content of each component are all expressed in weight percentage (wt%), that is, the content and total content of each component are expressed in weight percentage relative to the total amount of glass material converted into oxide composition. Here, the "composition converted into oxide" means that when the oxides, complex salts and hydroxides used as raw materials for the optical glass components of the present invention decompose and transform into oxides during melting, the total amount of the oxide material is taken as 100%.
[0031] Unless otherwise specified in specific circumstances, the numerical ranges listed in the present invention include upper and lower limits, "above" and "below" include endpoint values, and all integers and fractions included in the range, without being limited to the specific values listed when the range is defined. "And / or" referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.
[0032] <Essential Components and Optional Components>
[0033] SiO2 is the skeleton of optical glass. As a glass network generator, it has the function of maintaining the chemical stability of glass and improving the resistance of glass to devitrification. In the present invention, the above effect is obtained by containing more than 25% SiO2. Preferably, the content of SiO2 is more than 28%, and more preferably, the content of SiO2 is more than 29%. If the content of SiO2 is higher than 35%, the glass meltability is reduced, vitrification is difficult, and it is easy to form stones and other inherent quality problems. At the same time, the transition temperature of the glass rises, and too high a melting temperature will also cause the light transmittance of the glass to deteriorate. Therefore, the upper limit of the content of SiO2 is 35%, preferably 33%, and more preferably 32%.
[0034] B2O3 can improve the melting property and resistance to devitrification of glass, but when its content is too high, the chemical stability of glass decreases and the thermal expansion coefficient is adversely affected. Therefore, the content of B2O3 in the present invention is 0-8%, preferably 1-6%, and more preferably 2-5%.
[0035] Al2O3 can improve the chemical stability of glass, and increase the mechanical strength and weather resistance of glass, but when its content is too high, the meltability of glass decreases and the anti-crystallization performance deteriorates. Therefore, the content of Al2O3 is 0-8%, preferably 1-6%, and more preferably 2-5%.
[0036] ZrO2 can improve the hardness, refractive index and chemical stability of optical glass, reduce the thermal expansion coefficient of glass, and optimize high-temperature viscosity. When the content of ZrO2 is too high, the resistance to devitrification of glass decreases, the difficulty of melting increases, the melting temperature rises, and inclusions appear inside the glass and the light transmittance decreases. Therefore, the content of ZrO2 in the present invention is 2-10%, preferably 3-8%, and more preferably 4-6%.
[0037] BaO can increase the refractive index of glass, improve the thermal expansion coefficient and high temperature viscosity of glass, but if its content is too high, the chemical stability of glass will be deteriorated. Therefore, the content of BaO is limited to 35-45%, preferably 36-43%, and more preferably 37-41%.
[0038] In some embodiments, the ratio (SiO2+BaO) / (ZrO2+Al2O3) between the total content of SiO2 and BaO SiO2+BaO and the total content of ZrO2 and Al2O3 ZrO2+Al2O3 is controlled within the range of 3.5 to 15.0, which can reduce the thermal expansion coefficient of the glass and prevent the chemical stability of the glass from deteriorating. Therefore, it is preferred that (SiO2+BaO) / (ZrO2+Al2O3) is 3.5 to 15.0, and it is more preferred that (SiO2+BaO) / (ZrO2+Al2O3) is 4.0 to 10.5. Furthermore, by controlling (SiO2+BaO) / (ZrO2+Al2O3) within the range of 5.0 to 10.0, the striation degree of the glass can be further optimized. Therefore, it is further preferred that (SiO2+BaO) / (ZrO2+Al2O3) is 5.0 to 10.0, and it is further preferred that (SiO2+BaO) / (ZrO2+Al2O3) is 6.0 to 9.5.
[0039] CaO helps to improve the refractive index and hardness of glass and optimize the abrasiveness of glass, but if the content of CaO is too high, the anti-crystallization performance of glass will decrease. Therefore, the content of CaO is 0-5%, preferably 0-3%, and more preferably 0.1-2%.
[0040] SrO can adjust the refractive index and Abbe number of glass, but if its content is too high, the chemical stability of glass will be reduced, and the cost of glass will also rise rapidly. Therefore, the content of SrO is limited to 0-5%, preferably 0-2%, and more preferably 0-1%. In some embodiments, it is further preferred that SrO is not contained.
[0041] In some embodiments, the ratio of the total content of SiO2, CaO, and SrO (SiO2+CaO+SrO) to the content of BaO (SiO2+CaO+SrO) / BaO) is controlled within the range of 0.56 to 1.05, which can optimize the high temperature viscosity and striae of the glass. Therefore, it is preferred that (SiO2+CaO+SrO) / BaO is 0.56 to 1.05, more preferably (SiO2+CaO+SrO) / BaO is 0.6 to 1.0, further preferably (SiO2+CaO+SrO) / BaO is 0.65 to 0.95, and further preferably (SiO2+CaO+SrO) / BaO is 0.7 to 0.95.
[0042] MgO can reduce the relative partial dispersion of glass, but when the MgO content is too high, the refractive index of the glass is difficult to meet the design requirements, and the anti-crystallization performance and stability of the glass are reduced. Therefore, the MgO content is limited to 0-5%, preferably 0-2%, and more preferably 0-1%. In some embodiments, it is further preferred that MgO is not contained.
[0043] In some embodiments, the ratio (MgO+CaO+SrO) / ZrO2 between the total content of MgO, CaO, and SrO and the content of ZrO2 is controlled to be below 1.5, which can prevent the glass transition temperature from increasing while optimizing the anti-crystallization performance and light transmittance of the glass. Therefore, it is preferred that (MgO+CaO+SrO) / ZrO2 is below 1.5, more preferably (MgO+CaO+SrO) / ZrO2 is below 1.0, further preferably (MgO+CaO+SrO) / ZrO2 is 0.02 to 0.8, and further preferably (MgO+CaO+SrO) / ZrO2 is 0.05 to 0.5.
[0044] TiO2 has the effect of increasing the refractive index and dispersion of glass. A proper amount of TiO2 can make the glass more stable and reduce the viscosity of the glass. If the content of TiO2 is too high, the crystallization tendency of the glass increases and the transition temperature rises. Therefore, the content of TiO2 in the present invention is 3 to 12%, preferably 5 to 10%, and more preferably 6 to 9%.
[0045] In some embodiments, controlling the ratio of TiO2 / (CaO+Al2O3) between the content of TiO2 and the total content of CaO and Al2O3 (CaO+Al2O3) in the range of 0.5 to 6.0 is beneficial to reducing the density of the glass and preventing the deterioration of the anti-crystallization performance of the glass. Therefore, preferably TiO2 / (CaO+Al2O3) is 0.5 to 6.0, and more preferably TiO2 / (CaO+Al2O3) is 0.7 to 5.0. Furthermore, controlling TiO2 / (CaO+Al2O3) in the range of 0.8 to 4.0 can also optimize the striation degree of the glass. Therefore, it is further preferred that TiO2 / (CaO+Al2O3) is 0.8 to 4.0, and it is further preferred that TiO2 / (CaO+Al2O3) is 1.0 to 3.0.
[0046] In some embodiments, the ratio ZrO2 / (CaO+TiO2+Al2O3) between the content of ZrO2 and the total content of CaO, TiO2, and Al2O3 (CaO+TiO2+Al2O3) is controlled within the range of 0.2 to 1.5, which can optimize the thermal expansion coefficient and weather resistance of the glass and improve the bubble degree of the glass. Therefore, ZrO2 / (CaO+TiO2+Al2O3) is preferably 0.2 to 1.5, more preferably ZrO2 / (CaO+TiO2+Al2O3) is 0.4 to 1.0, further preferably ZrO2 / (CaO+TiO2+Al2O3) is 0.45 to 0.9, and further preferably ZrO2 / (CaO+TiO2+Al2O3) is 0.5 to 0.8.
[0047] ZnO can adjust the refractive index and dispersion of glass, reduce the transition temperature of glass, and allow glass to be melted at a lower temperature, thereby increasing the light transmittance of glass. If the ZnO content is too high, the high-temperature viscosity of the glass will increase, the difficulty of glass molding will increase, and the anti-crystallization performance will deteriorate. Therefore, the ZnO content is 6-15%, preferably 8-12%, and more preferably 9-11%.
[0048] In some embodiments, the ratio (CaO+SrO) / ZnO between the total content of CaO and SrO CaO+SrO and the content of ZnO is controlled to be below 1.0, so as to optimize the light transmittance and high temperature viscosity of the glass and prevent the thermal expansion coefficient of the glass from increasing. Therefore, preferably (CaO+SrO) / ZnO is below 1.0, more preferably (CaO+SrO) / ZnO is below 0.8, further preferably (CaO+SrO) / ZnO is below 0.5, and further preferably (CaO+SrO) / ZnO is 0.01 to 0.3.
[0049] Li2O can lower the transition temperature of glass, adjust the high temperature viscosity of glass, and improve the solubility of glass, but its high content is detrimental to the chemical stability and cost economy of glass. Therefore, the content of Li2O in the present invention is 5% or less, preferably 2% or less, and more preferably 1% or less. In some embodiments, it is further preferred that Li2O is not contained.
[0050] In some embodiments, the ratio of BaO content to the total content of SiO2, B2O3, Li2O, CaO, and SrO (SiO2+B2O3+Li2O+CaO+SrO) is controlled within the range of 0.65 to 1.5, which can improve the bubble degree and weather resistance of the glass and prevent the density of the glass from increasing. Therefore, the preferred BaO / (SiO2+B2O3+Li2O+CaO+SrO) is 0.65~1.5, the more preferred BaO / (SiO2+B2O3+Li2O+CaO+SrO) is 0.7~1.4, the further preferred BaO / (SiO2+B2O3+Li2O+CaO+SrO) is 0.8~1.3, and the further preferred BaO / (SiO2+B2O3+Li2O+CaO+SrO) is 0.9~1.2.
[0051] Na2O has the function of improving the fusibility of glass and can improve the melting effect of glass. If the content of Na2O is too high, the chemical stability and weather resistance of glass will be reduced. Therefore, the content of Na2O is 0-5%, preferably 0-3%, and more preferably 0.1-2%.
[0052] In some embodiments, the ratio (CaO+TiO2) / Na2O between the total content of CaO and TiO2 CaO+TiO2 and the content of Na2O is controlled within the range of 2.0 to 20.0, which can improve the chemical stability and anti-devitrification of the glass and prevent the light transmittance of the glass from deteriorating. Therefore, preferably (CaO+TiO2) / Na2O is 2.0 to 20.0, more preferably (CaO+TiO2) / Na2O is 4.5 to 16.0, further preferably (CaO+TiO2) / Na2O is 5.0 to 15.0, and further preferably (CaO+TiO2) / Na2O is 5.0 to 10.0.
[0053] K2O has the effect of improving the thermal stability and melting property of glass, but if its content exceeds 5%, the devitrification resistance and chemical stability of glass deteriorate. Therefore, the content of K2O in the present invention is 0-5%, preferably 0-2%, more preferably 0-1%. In some embodiments, it is further preferred that K2O is not contained.
[0054] In some embodiments, controlling the ratio of the total content of Li2O, Na2O, and K2O, Li2O+Na2O+K2O, to the content of ZrO2, (Li2O+Na2O+K2O) / ZrO2, to be below 1.0 is beneficial for obtaining the desired optical constants and optimizing the high temperature viscosity and weather resistance of the glass. Therefore, preferably (Li2O+Na2O+K2O) / ZrO2 is below 1.0, more preferably (Li2O+Na2O+K2O) / ZrO2 is below 0.7, further preferably (Li2O+Na2O+K2O) / ZrO2 is 0.02 to 0.5, and further preferably (Li2O+Na2O+K2O) / ZrO2 is 0.1 to 0.4.
[0055] Nb2O5 can increase the refractive index of glass, improve the chemical stability and resistance to devitrification of glass, but if its content is too high, the dispersion of glass will increase, and it will be difficult to obtain glass with target optical constants. At the same time, the cost and density of glass will increase, and the short-wave transmittance in the visible light region will decrease. Therefore, the content of Nb2O5 in the present invention is 5% or less, preferably 2% or less, and more preferably 1% or less. In some embodiments, it is further preferred that Nb2O5 is not contained.
[0056] WO3 can improve the refractive index and mechanical strength of glass. If the content of WO3 exceeds 5%, the thermal stability of glass decreases and the resistance to devitrification decreases. Therefore, the upper limit of WO3 content is 5%, preferably 2%, and more preferably 1%. In some embodiments, it is further preferred that WO3 is not contained.
[0057] Ln2O3 (Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3) is a component that improves the refractive index and chemical stability of glass. By controlling the content of Ln2O3 to be below 8%, the devitrification resistance of glass can be prevented from decreasing. Preferably, the upper limit of the content of Ln2O3 is 5%, and more preferably, the upper limit is 2%. In some embodiments, it is further preferred that Ln2O3 is not contained.
[0058] In some embodiments, controlling Ln2O3 / TiO2 to be below 0.4 can prevent the weather resistance and chemical stability of the glass from being reduced and optimize the high temperature viscosity of the glass. Therefore, Ln2O3 / TiO2 is preferably below 0.4, more preferably below 0.3, further preferably below 0.2, and even more preferably below 0.1.
[0059] In some embodiments, the ratio (B2O3+Ln2O3) / ZrO2 between the total content of B2O3 and Ln2O3 B2O3+Ln2O3 and the content of ZrO2 is controlled to be below 3.5, which can prevent the chemical stability of the glass from deteriorating while lowering the transition temperature of the glass. Therefore, it is preferred that (B2O3+Ln2O3) / ZrO2 is below 3.5. Furthermore, by controlling (B2O3+Ln2O3) / ZrO2 within the range of 0.1 to 3.0, the bubble degree of the glass can be further optimized. Therefore, it is more preferred that (B2O3+Ln2O3) / ZrO2 is 0.1 to 3.0, further preferred that (B2O3+Ln2O3) / ZrO2 is 0.2 to 2.5, and further preferred that (B2O3+Ln2O3) / ZrO2 is 0.3 to 1.5.
[0060] In some embodiments, the ratio of the total content of CaO, SrO, K2O and Ln2O3 (CaO+SrO+K2O+Ln2O3) to the content of Al2O3 (CaO+SrO+K2O+Ln2O3) / Al2O3) is controlled to be below 2.0, which can improve the hardness and anti-crystallization performance of the glass while preventing the bubble degree of the glass from deteriorating and preventing the transition temperature from increasing. Therefore, it is preferred that (CaO+SrO+K2O+Ln2O3) / Al2O3 is below 2.0, more preferably (CaO+SrO+K2O+Ln2O3) / Al2O3 is below 1.5, further preferably (CaO+SrO+K2O+Ln2O3) / Al2O3 is below 1.1, and further preferably (CaO+SrO+K2O+Ln2O3) / Al2O3 is 0.02 to 0.8.
[0061] In the present invention, by containing 0-1% of one or more components of Sb2O3, SnO, SnO2, and CeO2 as a clarifier, the clarification effect of the glass can be improved and the bubble degree of the glass can be improved. The content of the clarifier is preferably 0-0.5%, and the content of the clarifier is more preferably 0-0.2%. Sb2O3 is preferably used as a clarifier. When the content of Sb2O3 exceeds 1%, the clarification performance of the glass tends to decrease. At the same time, due to its strong oxidizing effect, it promotes the corrosion of the platinum or platinum alloy vessel for melting glass and the deterioration of the forming mold. Therefore, the content of Sb2O3 in the present invention is preferably 0-1%, more preferably 0-0.5%, and further preferably 0-0.2%. SnO and SnO2 can also be used as clarifiers, but when their content exceeds 1%, the tendency of the glass to color increases, or when the glass is heated, softened, and molded again, Sn will become the starting point of crystal nucleation, resulting in a tendency to devitrification. Therefore, the content of SnO2 in the present invention is preferably 0-1%, more preferably 0-0.5%, further preferably 0-0.2%, and further preferably does not contain SnO2; the content of SnO is preferably 0-1%, more preferably 0-0.5%, further preferably 0-0.2%, and further preferably does not contain SnO. The role and content ratio of CeO2 are consistent with those of SnO2, and its content is preferably 0-1%, more preferably 0-0.5%, further preferably 0-0.2%, and further preferably does not contain CeO2.
[0062] <Components that should not be contained>
[0063] In the glass of the present invention, even if oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo are contained alone or in combination in small amounts, the glass will be colored and absorption will occur at specific wavelengths in the visible light region, thereby weakening the property of the present invention of improving the visible light transmittance. Therefore, it is preferably substantially free of oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo, especially for optical glasses that require transmittance at wavelengths in the visible light region.
[0064] The oxides of Th, Cd, Tl, Os, Be and Se have a tendency to be controlled in recent years as harmful chemical substances, and environmental protection measures are necessary not only in the manufacturing process of glass, but also in the processing process and the disposal after productization. Therefore, in the case of paying attention to the impact on the environment, it is preferred that they are not actually contained except for being inevitably mixed in. Thus, the optical glass does not actually contain substances that pollute the environment. Therefore, even if special environmental countermeasures are not taken, the optical glass of the present invention can be manufactured, processed and discarded.
[0065] In order to achieve environmental friendliness, the optical glass of the present invention preferably does not contain As2O3 and PbO.
[0066] The "does not contain" and "0%" recorded in this article mean that the compound, molecule or element is not intentionally added as a raw material to the optical glass of the present invention; however, as raw materials and / or equipment for producing optical glass, there will be certain impurities or components that are not intentionally added, which will be contained in a small amount or trace amount in the final optical glass, and this situation is also within the scope of protection of the patent of this invention.
[0067] Next, the properties of the optical glass of the present invention will be described.
[0068] <Refractive Index and Abbe Number>
[0069] The refractive index of optical glass (n d ) and the Abbe number (ν d ) Tested according to the method specified in GB / T 7962.1-2010.
[0070] In some embodiments, the refractive index (n d ) has a lower limit of 1.67, a preferred lower limit of 1.68, and a more preferred lower limit of 1.69.
[0071] In some embodiments, the refractive index (n d ) has an upper limit of 1.73, a preferred upper limit of 1.72, and a more preferred upper limit of 1.71.
[0072] In some embodiments, the Abbe number (ν d ) has a lower limit of 38, a preferred lower limit of 39, and a more preferred lower limit of 40.5.
[0073] In some embodiments, the Abbe number (ν d ) has an upper limit of 45, a preferred upper limit of 44, and a more preferred upper limit of 42.5.
[0074] <density>
[0075] The density (ρ) of optical glass is tested according to the method specified in GB / T7962.20-2010.
[0076] In some embodiments, the density (ρ) of the optical glass of the present invention is 4.10 g / cm 3 Below, preferably 4.00 g / cm 3 Below, more preferably 3.90g / cm 3 the following.
[0077] <Coefficient of Thermal Expansion>
[0078] Thermal expansion coefficient of optical glass (α 100 / 300℃) The data at 100-300℃ were tested according to the method specified in GB / T7962.16-2010.
[0079] In some embodiments, the thermal expansion coefficient (α 100 / 300℃ ) is 95×10 -7 / K or less, preferably 90×10 -7 / K or less, more preferably 85×10 -7 / K or less.
[0080] <Water resistance stability>
[0081] Water resistance stability of optical glass (D W ) (Powder method) Tested in accordance with the method specified in GB / T 17129.
[0082] In some embodiments, the water resistance stability (D W ) is 2 or more types, preferably 1 type.
[0083] <Acid resistance stability>
[0084] Acid resistance stability of optical glass (D A ) (Powder method) Tested in accordance with the method specified in GB / T 17129.
[0085] In some embodiments, the acid resistance stability (D A ) is 2 or more types, preferably 1 type.
[0086] <Weather resistance>
[0087] The test method for weather resistance (CR) of optical glass is as follows: place the sample in a test box with a saturated water vapor environment of 90% relative humidity, alternately cycle every 1 hour at 40-50°C, and cycle for 15 cycles. The weather resistance category is divided according to the change in turbidity before and after the sample is placed. The weather resistance classification is shown in Table 1:
[0088] Table 1.
[0089]
[0090] In some embodiments, the weather resistance (CR) of the optical glass of the present invention is Class 2 or higher, preferably Class 1.
[0091] <Bubble Degree>
[0092] The bubble degree of optical glass is tested according to the method specified in GB / T7962.8-2010.
[0093] In some embodiments, the bubble degree of the optical glass of the present invention is above grade A, preferably above grade A0, and more preferably above grade A1. 00 class.
[0094] <Transition Temperature>
[0095] Transition temperature of optical glass (T g ) The test shall be carried out in accordance with the method specified in GB / T7962.16-2010.
[0096] In some embodiments, the transition temperature (T g ) is 680°C or lower, preferably 670°C or lower, and more preferably 665°C or lower.
[0097] <Crystallization upper limit temperature>
[0098] The anti-crystallization performance of optical glass was determined by the gradient temperature furnace method. The glass was made into a 180×10×10mm sample, polished on the side, and placed in a furnace with a temperature gradient (10℃ / cm) and a highest temperature zone of 1200℃ for 4 hours. Then the sample was taken out and naturally cooled to room temperature. The crystallization of the glass was observed under a microscope. The highest temperature corresponding to the appearance of crystals in the glass was the upper limit temperature of crystallization of the glass.
[0099] In some embodiments, the optical glass of the present invention has an upper limit crystallization temperature of 1100° C. or lower, preferably 1080° C. or lower, and more preferably 1070° C. or lower.
[0100] <Striation Degree>
[0101] The striation degree of the glass of the present invention is measured according to the method specified in MLL-G-174B. The method is to use a striation meter composed of a point light source and a lens, and compare and inspect with a standard sample from the direction where the striations are most easily visible. There are 4 levels in total, namely A, B, C, and D. Level A means no striations visible to the naked eye under the specified detection conditions, level B means fine and scattered striations under the specified detection conditions, level C means slight parallel striations under the specified detection conditions, and level D means rough striations under the specified detection conditions.
[0102] In some embodiments, the striae degree of the optical glass of the present invention is C level or higher, preferably B level or higher.
[0103] <High temperature viscosity>
[0104] The high temperature viscosity of optical glass is tested by the following method: The high temperature viscosity of glass is tested using THETA Rheotronic II high temperature viscometer using a rotation method. The unit of value is dPaS (poise). The smaller the value, the lower the viscosity.
[0105] In some embodiments, the viscosity of the optical glass of the present invention at 1400° C. is 50 poise or less, preferably 1 to 40 poise, and more preferably 2 to 20 poise.
[0106] <Light transmittance>
[0107] Light transmittance of optical glass (τ 400nm ) The test shall be carried out according to the method specified in GB / T 7962.12-2010.
[0108] In some embodiments, the optical glass of the present invention has a light transmittance (τ 400nm ) is 92.0% or more, preferably 93.0% or more, more preferably 94.0% or more, and further preferably 95.0% or more.
[0109] [Method for producing optical glass]
[0110] The manufacturing method of the optical glass of the present invention is as follows: the glass of the present invention is produced using conventional raw materials and processes, including but not limited to using oxides, hydroxides, complex salts (such as carbonates, nitrates, sulfates, etc.), boric acid, etc. as raw materials, and after the ingredients are prepared according to the conventional method, the prepared furnace materials are put into a melting furnace (such as platinum or platinum alloy crucible) at 1200-1400°C for melting, and after clarification and homogenization, a homogeneous molten glass without bubbles and undissolved substances is obtained, and the molten glass is cast in a mold and annealed. Those skilled in the art can appropriately select raw materials, process methods and process parameters according to actual needs.
[0111] [Glass preforms and optical components]
[0112] The prepared optical glass can be used to make a glass preform by means of direct drop molding, grinding, or compression molding such as hot press molding. That is, the molten optical glass can be directly precision drop molded into a glass precision preform, or the glass preform can be made by mechanical processing such as grinding and grinding, or the preform for compression molding made of the optical glass can be made by hot press molding and then grinding. It should be noted that the means for preparing the glass preform are not limited to the above means.
[0113] As described above, the optical glass of the present invention is useful for various optical elements and optical designs, and it is particularly preferred to form a preform from the optical glass of the present invention and use the preform to perform re-hot pressing, precision stamping, etc. to produce optical elements such as lenses and prisms.
[0114] The glass preform and optical element of the present invention are both formed of the optical glass of the present invention. The glass preform of the present invention has the excellent properties of optical glass; the optical element of the present invention has the excellent properties of optical glass, and can provide various optical elements such as lenses and prisms with high optical value.
[0115] Examples of the lens include various lenses having spherical or aspherical lens surfaces, such as a concave meniscus lens, a convex meniscus lens, a biconvex lens, a biconcave lens, a plano-convex lens, and a plano-concave lens.
[0116] [Optical instruments]
[0117] The optical element formed by the optical glass of the present invention can be used to manufacture optical instruments such as photographic equipment, video equipment, projection equipment, display equipment, vehicle-mounted equipment and monitoring equipment.
[0118] Example
[0119] <Optical Glass Example>
[0120] In order to further clearly illustrate and describe the technical solution of the present invention, the following non-limiting examples are provided.
[0121] This embodiment adopts the above optical glass manufacturing method to obtain optical glasses having the compositions shown in Tables 2 to 4. In addition, the properties of each glass are measured by the testing method described in the present invention, and the measurement results are shown in Tables 2 to 4.
[0122] Table 2.
[0123]
[0124]
[0125] Table 3.
[0126]
[0127]
[0128] Table 4.
[0129]
[0130]
[0131] <Glass Preform Example>
[0132] The glass obtained from optical glass examples 1 to 20# is used, for example, by grinding processing, or by molding methods such as hot pressing, precision stamping, etc., to make preforms of various lenses, prisms, etc., such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses.
[0133] <Optical Element Embodiment>
[0134] The preforms obtained in the above-mentioned glass preform embodiments are annealed to reduce the internal stress of the glass and fine-tune the refractive index so that the optical properties such as the refractive index reach the desired values.
[0135] Next, each preform is ground and polished to produce various lenses and prisms such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. The surface of the obtained optical element may be coated with an anti-reflection film.
[0136] <Optical Instrument Embodiment>
[0137] The optical element obtained by the above-mentioned optical element embodiment is optically designed to form an optical component or optical assembly by using one or more optical elements, and can be used in, for example, imaging equipment, sensors, microscopes, medical technology, digital projection, communications, optical communication technology / information transmission, optics / lighting in the automotive field, lithography technology, excimer lasers, wafers, computer chips, and integrated circuits and electronic devices including such circuits and chips.
Claims
1. Optical glass, characterized in that: Its components, expressed in weight percentage, include: SiO2: 25-35%; Al2O3: 0-8%; ZrO2: 2-10%; BaO: 35-45%; TiO2: 3-12%; and ZnO: 6-15%.
2. The optical glass according to claim 1, characterized in that: Its components, expressed in weight percentage, also contain: B2O3: 0-8%; and / or CaO: 0-5%; and / or SrO: 0-5%; and / or Na2O: 0-5%; and / or MgO: 0-5%; and / or Li2O: 0-5%; and / or K2O: 0-5%; and / or WO3: 0-5%; and / or Nb2O5: 0-5%; and / or Ln2O3: 0-8%; and / or clarifier: 0-1%, wherein the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3, and the clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2.
3. Optical glass, characterized in that: Its components, expressed in weight percentage, are SiO2: 25-35%; Al2O3: 0-8%; ZrO2: 2-10%; BaO: 35-45%; TiO2: 3-12%; ZnO: 6-15%; B2O3: 0-8%; CaO: 0-5%; SrO: 0~5%; Na2O: 0~5%; MgO: 0~5%; Li2O: 0~5%; K2O: 0~5%; WO3: 0~5%; Nb2O5: 0~5%; Ln2O3: 0~8%; Clarifier: 0-1% composition, the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, Lu2O3, and the clarifier is one or more of Sb2O3, SnO, SnO2, CeO2.
4. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: (SiO2+BaO) / (ZrO2+Al2O3) is 3.5~15.0, preferably (SiO2+BaO) / (ZrO2+Al2O3) is 4.0~10.5, more preferably (SiO2+BaO) / (ZrO2+Al2O3) is 5.0~10.0, and further preferably (SiO2+BaO) / (ZrO2+Al2O3) is 6.0~9.
5.
5. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: TiO2 / (CaO+Al2O3) is 0.5-6.0, preferably TiO2 / (CaO+Al2O3) is 0.7-5.0, more preferably TiO2 / (CaO+Al2O3) is 0.8-4.0, and further preferably TiO2 / (CaO+Al2O3) is 1.0-3.
0.
6. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: ZrO2 / (CaO+TiO2+Al2O3) is 0.2~1.5, preferably ZrO2 / (CaO+TiO2+Al2O3) is 0.4~1.0, more preferably ZrO2 / (CaO+TiO2+Al2O3) is 0.45~0.9, and further preferably ZrO2 / (CaO+TiO2+Al2O3) is 0.5~0.
8.
7. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: (SiO2+CaO+SrO) / BaO is 0.56-1.05, preferably (SiO2+CaO+SrO) / BaO is 0.6-1.0, more preferably (SiO2+CaO+SrO) / BaO is 0.65-0.95, and further preferably (SiO2+CaO+SrO) / BaO is 0.7-0.
95.
8. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: (MgO+CaO+SrO) / ZrO2 is less than 1.5, preferably (MgO+CaO+SrO) / ZrO2 is less than 1.0, more preferably (MgO+CaO+SrO) / ZrO2 is 0.02~0.8, and further preferably (MgO+CaO+SrO) / ZrO2 is 0.05~0.
5.
9. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: (CaO+SrO) / ZnO is less than 1.0, preferably (CaO+SrO) / ZnO is less than 0.8, more preferably (CaO+SrO) / ZnO is less than 0.5, and further preferably (CaO+SrO) / ZnO is 0.01-0.
3.
10. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: BaO / (SiO2+B2O3+Li2O+CaO+SrO) is 0.65-1.5, preferably BaO / (SiO2+B2O3+Li2O+CaO+SrO) is 0.7-1.4, more preferably BaO / (SiO2+B2O3+Li2O+CaO+SrO) is 0.8-1.3, and further preferably BaO / (SiO2+B2O3+Li2O+CaO+SrO) is 0.9-1.
2.
11. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: (Li2O+Na2O+K2O) / ZrO2 is less than 1.0, preferably (Li2O+Na2O+K2O) / ZrO2 is less than 0.7, more preferably (Li2O+Na2O+K2O) / ZrO2 is 0.02~0.5, and further preferably (Li2O+Na2O+K2O) / ZrO2 is 0.1~0.
4.
12. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: Ln2O3 / TiO2 is less than 0.4, preferably Ln2O3 / TiO2 is less than 0.3, more preferably Ln2O3 / TiO2 is less than 0.2, and further preferably Ln2O3 / TiO2 is less than 0.1, and the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3.
13. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: (B2O3+Ln2O3) / ZrO2 is less than 3.5, preferably (B2O3+Ln2O3) / ZrO2 is 0.1-3.0, more preferably (B2O3+Ln2O3) / ZrO2 is 0.2-2.5, and further preferably (B2O3+Ln2O3) / ZrO2 is 0.3-1.5, and the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3.
14. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: (CaO+SrO+K2O+Ln2O3) / Al2O3 is less than 2.0, preferably (CaO+SrO+K2O+Ln2O3) / Al2O3 is less than 1.5, more preferably (CaO+SrO+K2O+Ln2O3) / Al2O3 is less than 1.1, and further preferably (CaO+SrO+K2O+Ln2O3) / Al2O3 is 0.02-0.8, and the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3.
15. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: (CaO+TiO2) / Na2O is 2.0-20.0, preferably (CaO+TiO2) / Na2O is 4.5-16.0, more preferably (CaO+TiO2) / Na2O is 5.0-15.0, and further preferably (CaO+TiO2) / Na2O is 5.0-10.
0.
16. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: SiO2: 28-33%, preferably SiO2: 29-32%; and / or Al2O3: 1-6%, preferably Al2O3: 2-5%; and / or ZrO2: 3-8%, preferably ZrO2: 4-6%; and / or BaO: 36-43%, preferably BaO: 37-41%; and / or CaO: 0-3%, preferably CaO: 0.1-2%; and / or SrO: 0-2%, preferably SrO: 0-1%; and / or TiO2: 5-10%, preferably TiO2: 6-9%; and / or ZnO: 8-12%, preferably ZnO: 9-11%; and / or Na2O: 0-3%, preferably Na2O: 0.1-2%; and / or B2O3: 1-6%, preferably Select B2O3: 2-5%; and / or MgO: 0-2%, preferably MgO: 0-1%; and / or Li2O: 0-2%, preferably Li2O: 0-1%; and / or K2O: 0-2%, preferably K2O: 0-1%; and / or WO3: 0-2%, preferably WO3: 0-1%; and / or Nb2O5: 0-2%, preferably Nb2O5: 0-1%; and / or Ln2O3: 0-5%, preferably Ln2O3: 0-2%; and / or clarifier: 0-0.5%, preferably clarifier: 0-0.2%, wherein Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3, and the clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2.
17. The optical glass according to any one of claims 1 to 3, characterized in that: Its components do not contain MgO; and / or do not contain SrO; and / or do not contain Li2O; and / or do not contain K2O; and / or do not contain WO3; and / or do not contain Nb2O5; and / or do not contain SnO2; and / or do not contain SnO; and / or do not contain CeO2; and / or do not contain As2O3; and / or do not contain PbO; and / or do not contain Ln2O3, wherein Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3.
18. The optical glass according to any one of claims 1 to 3, characterized in that: The refractive index n of the optical glass d is 1.67 to 1.73, preferably 1.68 to 1.72, more preferably 1.69 to 1.71, and the Abbe number v d It is 38 to 45, preferably 39 to 44, and more preferably 40.5 to 42.
5.
19. The optical glass according to any one of claims 1 to 3, characterized in that: The density of the optical glass is 4.10 g / cm 3 Below, preferably 4.00 g / cm 3 Below, more preferably 3.90g / cm 3 Below; and / or thermal expansion coefficient α 100 / 300℃ 95×10 -7 / K or less, preferably 90×10 -7 / K or less, more preferably 85×10 -7 / K or less; and / or water resistance stability D W 2 or more, preferably 1; and / or acid resistance stability D A The weather resistance CR is 2 or more, preferably 1; and / or the air bubble degree is A or more, preferably A0 or more, more preferably A 00 level; and / or transition temperature T g is 680°C or less, preferably 670°C or less, more preferably 665°C or less; and / or the crystallization upper limit temperature is 1100°C or less, preferably 1080°C or less, more preferably 1070°C or less; and / or the striae is C or above, preferably B or above; and / or the viscosity at 1400°C is 50 poise or less, preferably 1 to 40 poise, more preferably 2 to 20 poise; and / or the light transmittance τ 400nm It is 92.0% or more, preferably 93.0% or more, more preferably 94.0% or more, and further preferably 95.0% or more.
20. A glass preform, characterized in that: Made of the optical glass described in any one of claims 1 to 19.
21. An optical element, characterized in that The optical glass is made of any one of claims 1 to 19, or the glass preform is made of claim 20.
22. An optical instrument, characterized in that Contains the optical glass according to any one of claims 1 to 19, and / or contains the optical element according to claim 21.
